Catalytic desulfurization of marine gas oil and marine diesel oil under methane environment. (1st April 2021) - Li, Yimeng; He, Peng; Li, Zhaofei; Xu, Hao; Jarvis, Jack; Meng, Shijun; Song, Hua
Graphical abstract: Highlights: Methane has a positive effect on desulfurization of low-sulfur fuel oil. 50% sulfur removal is achieved for marine gas oil and marine diesel oil. Less than 0.1% sulfur content is reached for both oils. Methane presence suppresses the over-cracking and coking formation. Abstract: The desulfurization of marine gas oil (MGO) and marine diesel oil (MDO) is crucial for the bunker fuel industry due to the new regulation on SOx emission imposed by the International Maritime Organization. The catalytic desulfurization of such feedstock is conducted under methane environment in this study. Using a ZSM-5 with uniform cylindrical morphology (UZSM-5) as the catalyst support material, the over-cracking of oil molecules is inhibited. The incorporation of Ga and Mo enhances the activation of methane, aromatization of the feedstock and conversion of sulfur containing groups, particularly when marine diesel oil with a higher sulfur content is charged as the feed. Under CH4 environment, 58.8% sulfur content in the feedstock is converted comparing with that of 42.8% under N2 environment when Ga-Mo/UZSM-5 is employed as the catalyst. The participation of methane not only improves the desulfurization performance, but also suppresses coking and over-cracking of the feedstock as well as increasing the liquid product yield probably through methane incorporation to the product molecules.